The Queen of Spades. Codes of Plastic Visuality - Tatiana A. Boborykina (Достоевский и мировая культура: Филологический журнал)
In accordance with the title the essay explores some of the key moments of Alexander Pushkin’s The Queen of Spades, which are this way or other encoded. Their decoding may serve to a better understanding of both the author’s artistic method and the message of his story. These verbal codes sometimes appear as visual or inwardly connected throughout the entire realm of the text. However, some of them remain unnoticed or simply disappear when translated into foreign languages. Even in certain publications in the native tongue they are for no reason omitted. Such negligence of those parts of the text which appear to be Pushkin’s “secret signs” can be explained by various reasons, including the fact that apparently unremarkable words, especially when placed at a distance from one another, are not recognized as being connected in a particular “stream of consciousness,” or as ciphers that contain important information. The essay explores some of the unnoticed codes of The Queen of Spades in various French and English translations. However, a reflection on these codes as well as the creation of new ones that discover the subtext of the short story can be found in its translations into the languages of visual arts. Some examples are given from Thorold Dickenson’s and Igor Maslennikov’s film versions as well as from the director’s interpretation of Tchaykovsky’s opera by Vsevolod Meyerhold, and a more detailed analysis is given to various visual metaphors and accordingly to the whole conception of the choreographic adaptation by Roland Petit of Pushkin’s short story. Depending on the method and approach chosen, each interpreter, while revealing some of the secret codes, creates yet another vision of The Queen of Spades. Summarizing some of the most popular interpretations, the author offers the one, according to which the main intrigue is not so much the card game, as the gambler’s consciousness and subconscious. This is where his almost “insane” plans are born and where his almost “criminal” actions that determine his “punishment” take place. The article explores the role of Herman in choosing his own Destiny and concludes that the main mystery of the story, told by Pushkin with a mastery far ahead of his time, is Man himself.